Characterisation of vacuum dried amniotic membrane and validation of the processing protocol - Marsit, Nagi Mohammed Abdalla (2019)
Amniotic membrane (AM) has been used for several decades as a wound healing material in different clinical applications. AM is prepared for usage in contact with damaged tissue, therefore, sterility is a crucial issue in AM manufacturing. There is no consensus on the optimal method for preparing and sterilising AM. AM obtained aseptically from elective caesarean section should have low bioburden, thus, a powerful processing and sterilisation methods is potentially not required. Therefore, development of a gentle processing protocol for AM can overcome the limitations of other processing methods such as cryopreservation and radiation sterilisation on AM structure and function.